2015
DOI: 10.1159/000370069
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Analysis of Host Responses to Marek's Disease Virus Infection in Chicken Thymus

Abstract: Marek's disease virus (MDV) is a cell-associated alpha-herpesvirus that causes T-cell lymphomas and nervous disorders in chickens. Different from other lymphoid organs, the thymus is the site of T-cell maturation and differentiation. However, the transcriptional response to MDV infection in the chicken thymus is still not known. In this study, we performed genome-wide expression analysis in thymus tissues of RB1B-infected chickens at different time points to investigate the molecular mechanisms of MDV pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
1
7
0
2
Order By: Relevance
“…This is well reflected in the molecular events elucidated in our present study where multiple significant pathways associated with gene transcription and translation, such as the ‘Ribosome’, ‘Ribosome biogenesis in eukaryotes’, ‘Spliceosome’, ‘RNA transport’ and ‘mRNA surveillance pathway’, were enriched during 3–4 weeks post GaHV2 infection. This is similar, but more extensive, to a previous report in which analogous pathways of ‘Protein transport’, ‘mRNA processing’ and ‘RNA splicing’ were significantly enriched at 21 and 28 dpi in thymus of GaHV2-infected birds 38 . In the process of protein synthesis, translation initiation is considered as a rate-limiting step and is governed by the availability and activity of EIFs 39 , amongst which EIF3 is the most complex member 40 .…”
Section: Discussionsupporting
confidence: 90%
“…This is well reflected in the molecular events elucidated in our present study where multiple significant pathways associated with gene transcription and translation, such as the ‘Ribosome’, ‘Ribosome biogenesis in eukaryotes’, ‘Spliceosome’, ‘RNA transport’ and ‘mRNA surveillance pathway’, were enriched during 3–4 weeks post GaHV2 infection. This is similar, but more extensive, to a previous report in which analogous pathways of ‘Protein transport’, ‘mRNA processing’ and ‘RNA splicing’ were significantly enriched at 21 and 28 dpi in thymus of GaHV2-infected birds 38 . In the process of protein synthesis, translation initiation is considered as a rate-limiting step and is governed by the availability and activity of EIFs 39 , amongst which EIF3 is the most complex member 40 .…”
Section: Discussionsupporting
confidence: 90%
“…A thorough but non-exhaustive literature search showed over 5,000 genes were reported from RNA-Seq and/or quantitative real-time PCR studies, which were dysregulated in expression under the induction of MDV challenge at varied stages [15,17,19,20,2224,27,28,4648]. In this study, a total of 203 genes were identified in the two genetic lines of chickens differentially expressed in response to MDV challenge under the controlled conditions at 5 DPI.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have employed RNA-Seq to explore gene expression profiles of chickens with MD [2729]. Despite the extensive efforts, molecular mechanisms of genetic resistance to MD, however, remain far from fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Son muchos los genes de las aves de los cuales se especula que están relacionados con la respuesta inmune e involucrados en la resistencia o la susceptibilidad frente al VEM, todos son sobre-expresados durante el proceso de replicación viral al interior de la célula y pueden inducir la formación de proteínas que ayudan al cambio morfológico de la célula 40,58 (Figura 2), MEDICINA VETERINARIA Y ZOOTECNIA Uno de los mayores efectos que tienen los genes asociados al virus es la de producir factores quimotácticos de células T para poder infectarlas permitiendo que se presente la enfermedad tumoral en las aves; algunos de los genes involucrados en la resistencia al VEM son la hormona de crecimiento (GH), antígeno 2 de células madre (SCA2) o precursor de antígeno de Linfocito (LY6E), cadena B del complejo mayor de histocompatibilidad por medio de la reducción de la expresión de las glicoproteínas del CMH B clase I (BLB o CD74), CD79B durante la replicación lítica viral como mecanismo de la evasión de la respuesta inmune, esta reducción en la expresión de las moléculas en la superficie celular no se presenta durante la latencia, sin embargo una expresión genómica mínima viral y la integración a los telómeros de la célula hospedera son suficientes para la evasión de la respuesta inmune 27,47,61 .…”
Section: Genes Asociados Con La Susceptibilidad Y Resistencia a La Enunclassified
“…Durante el proceso de defensa del hospedero contra el virus para permitir que el sistema inmune del ave pueda montar una respuesta efectiva genes como CTLA4, Interferón de tipo 1 (IFNA), Interferón tipo 2 (IFNG), interleucinas y receptores de interleucinas (IL-6, IL-8, IL-13R2A e IL18) 59,60 , quimoquinas proinflamatoria (CCLi7, CCL12, CCLi6, CCLi3, CCL17 y CCL19), respuesta factor regulatorio de interferón (IRF1, IFIH, IFIT-Like), óxido nítrico sintetasa inducible (NOS2A), Proteína específica de quiescencia (P20K), proteasa proinflamatoria granzina A (GZMA), receptor TLR3, TLR1B, TLR15 y TLR21, Lisozimas (LYG2), avidina (AVD), IRG1, MDV1, genes mitocondriales que codifican fosfoenolpiruvato carboxiquinasa, NADH deshidrogenasa subunidad 4, concavalina A, factor de mantenimiento de la latencia (LMF) actúan durante el proceso de defensa contra el virus y los efectos citopáticos sobre las células hospederas 19,56,58 .…”
Section: Genes Asociados Con La Susceptibilidad Y Resistencia a La Enunclassified